Pengaruh Biaya Promosi Terhadap Tingkat Jumlah Nasabah Tabungan Batara Pada PT Bank Tabungan Negara ( Persero) Cabang Bogor - Sari, Rita; Prabowo, Agung (Jurnal Ilmiah Ranggagading (JIR), 2003)
Promotion constitutes the most effective instrument as an effort to influences and appeal members of society to make use of firmâs services and products so that it will increase the number of clients or customers. In the frame of conducting its promotion, the firm (the bank) must understand as deep as possible about its own capability. Promotion could be conducted by means of media or increasing services to customers, namely by paying attention to customersâ pleasure in connection with their saving account